The impact of cash flow volatility on firm leverage and debt maturity structure: evidence from China. Issue 1 (19th February 2018) - Memon, Zulfiqar Ali; Chen, Yan; Tauni, Muhammad Zubair; Ali, Hashmat
Abstract : Purpose: The purpose of this paper is to investigate the influence of cash flow volatility on firm's leverage levels. It also analyzes how cash flow volatility influences the debt maturity structure for the Chinese listed firms. Design/methodology/approach: The authors construct the measure for cash flow variability as five-year rolling standard deviation of the cash flow from operations. The authors use generalized linear model approach to determine the effect of volatility on leverage. In addition, the authors design a categorical debt maturity variable and assign categories depending upon firm's usage of debt at various maturity levels. The authors apply Ordered Probit regression to analyze how volatility affects firm's debt maturity structure. The authors lag volatility and other independent variables in the estimation models so as to eliminate any possible endogeneity problems. Finally, the authors execute various techniques for verifying the robustness of the main findings. Findings: The authors provide evidence that higher volatility of cash flows results in lower leverage levels, while the sub-sampling analysis reveals that there is no such inverse association in the case of Chinese state-owned enterprises. The authors also provide novel findings that irrespective of the ownership structure, firms facing high volatility choose debt of relatively shorter maturities and vice versa. Overall, a rise of one standard deviation in volatility causes 8.89 percent reduction in long-term market leverage ratio and 26.62 percent reduction in the likelihood of issuing debentures or long-term notes. Research limitations/implications: This study advocates that cash flow volatility is an essential factor for determining both the debt levels and firm's term-to-maturity structure. The findings of this study can be helpful for the financial managers in maintaining optimal leverage and debt maturity structure, for lenders in reducing their risk of non-performing loans and for investors in their decision-making process. Originality/value: Existing empirical literature regarding the influence of variability of cash flows on leverage and debt maturity structure is inconclusive. Moreover, prior research studies mainly focus only on the developed countries. No previous comprehensive study exists so far for Chinese firms in this regard. This paper endeavors to fulfill this research gap by furnishing novel findings in the context of atypical and distinctive institutional setup of Chinese firms.